Pengaruh Terapi Musik Klasik Mozart terhadap Tingkat Emesis Gravidarum pada Ibu Hamil Trimester 1 di Wilayah Puskesmas Jakenan Kabupaten Pati - Munziyah, Dewi; Sri Hadi Sulistiyaningsih; Siti Marfuah (Pusat riset dan Inovasi Nasional, 2024)
Pregnancy is the process of fetal growth and development that occurs in the uterus from conception to the onset of labor. In the first trimester, mothers usually experience nausea and vomiting starting at around 8 weeks and ending at 12 weeks. Emesis gravidarum is nausea and vomiting that can cause discomfort and the frequency of nausea and vomiting occurs approximately 5 times a day, which occurs in the first trimester of pregnancy. This study aims to determine the Effect of Mozart Classical Music Therapy on the Level of Emesis Gravidarum in Pregnant Women in the First Trimester. The research design used in this study was pre-experimental with a one group pretest & posttest design approach. The population in this study were all pregnant women in the first trimester in the Jakenan Health Center Area, Pati Regency. The population used was 30 pregnant women in the first trimester. The number of pregnant women samples used in this study was 30 pregnant women, the instrument used was an observation sheet, the results of which will be analyzed using the Wilcoxon sign rank test method. The results showed that most of the frequency of emesis gravidarum before being given Mozart classical music intervention was in the moderate category, as many as 16 respondents (53.3%). Most of the frequency of emesis gravidarum after being given Mozart classical music intervention was in the mild category, as many as 20 respondents (66.7%) and almost some were moderate, as many as 10 respondents (33.3%). Data analysis shows that there is a difference in the level of emesis gravidarum before and after being given classical Mozart music therapy, a p value of 0.000 <α 0.05 is obtained, which means that classical Mozart music has an effect on reducing the frequency of emesis gravidarum in pregnant women in the first trimester in the Jakenan Health Center area, Pati Regency. It is hoped that health workers such as health center officers and midwives will improve their education and handling of reducing Emesis gravidarum in pregnant women non-pharmacologically.